2016
DOI: 10.1515/hukin-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Upper Respiratory Tract Diseases in Athletes in Different Sports Disciplines

Abstract: Upper respiratory tract diseases in athletes are a very common medical problem. Training conditions in different sports disciplines increase the risk of upper respiratory disease. Epidemiological evidence suggests that heavy acute or chronic exercise is related to an increased incidence of upper respiratory tract infections in athletes. Regular physical exercise at high intensity may lead to transient immunosuppression due to high prevalence of allergic diseases in athletes. Regardless of the cause they can ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 33 publications
2
19
0
3
Order By: Relevance
“…The management of airway hyper‐responsiveness and other upper respiratory tract diseases amongst elite athletes commonly includes the use of ® 2 ‐agonists, which necessitates the consideration of regulations established by WADA . These regulations have been the subject of intense debate, particularly concerning the use of (inhaled) salbutamol, which was recently shown to exhibit no effects on repeated sprint performance, dribbling, vertical jump, and passing amongst football players when administering the drug in permitted dosages .…”
Section: β2‐agonistsmentioning
confidence: 99%
“…The management of airway hyper‐responsiveness and other upper respiratory tract diseases amongst elite athletes commonly includes the use of ® 2 ‐agonists, which necessitates the consideration of regulations established by WADA . These regulations have been the subject of intense debate, particularly concerning the use of (inhaled) salbutamol, which was recently shown to exhibit no effects on repeated sprint performance, dribbling, vertical jump, and passing amongst football players when administering the drug in permitted dosages .…”
Section: β2‐agonistsmentioning
confidence: 99%
“…Зростання інтенсивності навантажень, зумовлене збільшенням обсягів тренувальних занять, кількістю змагань та їх важливістю, неминуче впливає на показники імунної резистентності спортсменів [1,2]. У сучасній науковій літературі вивчаються показники гуморального і клітинного імунітету спортсменів у спокої та в період тренувально-змагальної діяльності [3][4][5].…”
Section: вступunclassified
“…Так, зокрема спортсмени менше схильні до захворюваності на вірусні інфекції в холодний період року, рідше хворіють на тяжкі форми респіраторних вірусних інфекцій та грипу. Спортсмени переносять вірусні інфекційні захворювання в більш легкій формі і видужують протягом меншої кількості днів [2,8]. Одною з перспективних форм м'язової діяльності, яка дає змогу диференційовано підходити до побудови тренувального процесу та корекції величини фізичних навантажень з урахуванням індивідуальних вікових можливостей організму людини -є використання силового фітнесу [5].…”
Section: вступunclassified
“…Coaches and sport team physicians are interested in maintaining the health of their athletes during training and competition sessions. Epidemiological evidence suggests that heavy acute or chronic bouts of strenuous exercise correspond with an increased incidence of upper respiratory tract infections (URTI) that can negatively affect the health and performance of athletes (1). Previous research has particularly confirmed that intense exercise required in competitive sports is related to a threefold higher incidence of URTI (2).…”
Section: Introductionmentioning
confidence: 99%